2001
DOI: 10.1006/mthe.2001.0329
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cytokine Response to Systemic Adenoviral Vectors in Mice Is Mediated by Dendritic Cells and Macrophages

Abstract: We investigated the cellular basis for secretion of inflammatory cytokines in mice following intravenous administration of adenoviral vectors (Ad). Serum inflammatory cytokines including interleukin-6 (IL-6), IL-12, and tumor necrosis factor-alpha (TNF-alpha) were detected as early as 6 h following intravenous injection of Ad-expressing Escherichia coli beta-galactosidase (Ad-lacZ). Ad-lacZ readily accumulated in the splenic marginal zone 1 h after intravenous infusion, where both dendritic cells (DCs) and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
291
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(301 citation statements)
references
References 63 publications
10
291
0
Order By: Relevance
“…In vivo transduction of dendritic cells and macrophages by recombinant adenovirus has been previously described after i.v. 13,15 or i.m. injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo transduction of dendritic cells and macrophages by recombinant adenovirus has been previously described after i.v. 13,15 or i.m. injection.…”
Section: Discussionmentioning
confidence: 99%
“…gene transfer could be due to the well-known migration of donor DCs from the heart into the spleen and not mesenteric lymph nodes 18,19 after AdHO-1 transduction or due to the migration of adenoviral particles from the heart to the spleen where they could transduce recipient DCs or macrophages. 13 Finally, the inhibition of MLRs by non-T cells suggests that spleen APCs could mediate this inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been suggested that preferential activation of macrophages and dendritic cells by adenovirus leads to acute inflammatory response in mice. 48 There is a need to study the role of alginate microparticles in modulating immune response through macrophages and dendritic cells. It is believed that adenovirus will be released from microparticles slowly over a period, thereby reducing the toxicity mediated by the activation of macrophages and dendritic cells by adenovirus.…”
Section: Circumvention Of Vector-specific Immune Response Sailaja Et Almentioning
confidence: 99%